2020
DOI: 10.1101/2020.10.12.335810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synapse-specific direction selectivity in retinal bipolar cell axon terminals

Abstract: The ability to encode the direction of image motion is fundamental to our sense of vision. Direction selectivity along the four cardinal directions is thought to originate in direction-selective ganglion cells (DSGCs), due to directionally-tuned GABAergic suppression by starburst cells. Here, by utilizing two-photon glutamate imaging to measure synaptic release, we reveal that direction selectivity along all four directions arises earlier than expected, at bipolar cell outputs. Thus, DSGCs receive directionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…3), just as those studies observed. There is one recent study, however, that does not fit into this pattern: using glutamate imaging, they provided evidence for a specialized circuit that bestows "true" DS on a subset of axon terminals in type 2 and 7 BCs (46). Critically, that study found a contribution from wide-field ACs; thus, the mechanism is likely only engaged for large moving stimuli.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…3), just as those studies observed. There is one recent study, however, that does not fit into this pattern: using glutamate imaging, they provided evidence for a specialized circuit that bestows "true" DS on a subset of axon terminals in type 2 and 7 BCs (46). Critically, that study found a contribution from wide-field ACs; thus, the mechanism is likely only engaged for large moving stimuli.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, direction selective RGCs are known to play important roles in brain functions and behaviors involving global motion information (64,94,95). Previous studies have also suggested that BCs participate in direction detection via other mechanisms (for example see (19,31,32,35,46,57) but also (33,34,42)) which raises the question of how these mechanisms work together. Given the diverse stimuli often used to probe motion processing, it is possible that distinct mechanisms of direction detection are engaged under different environmental conditions (as previously suggested in (96,97)), which could 571 ensure robust DS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These neurons are the bridge between the photoreceptors and ganglion cells that deliver the results of retinal processing to downstream circuits 6 . The synaptic compartments of bipolar cells contribute to a number of processing tasks, from adaptive gain control to temporal filtering and the coding of motion, colour, orientation and direction 6,[16][17][18][19][20] . Bipolar cells, like sensory hair cells and electroreceptors, contain ribbon structures that supply vesicles to the active zone 21 .…”
Section: Discussionmentioning
confidence: 99%